Military Threats, International Pressure, and Public Opinion on the Nuclear Ban Treaty in Japan - Takaya Kanno; Hirofumi Miwa (Journal for Peace and Nuclear Disarmament)
This study examines the effect of perceived military threat on Japanese people’s opinion about Japan’s accession to the Treaty on the Prohibition of Nuclear Weapons. While nuclear aversion has been historically strong and deep-rooted in Japan, we expected that people would hesitate to support the treaty when reminded of the deteriorating security environment, considering recent experimental evidence suggesting that nuclear aversion is conditional and tends to fluctuate often and that Japanese citizens tend to be apathetic towards international laws. Moreover, we examine the possibility that pressure from foreign countries and international organizations reinforces people’s support for the treaty. Our survey experiment reveals that Japanese people are less likely to support Japan’s accedence to the treaty when they are primed with security threats, although the difference is small, and that this negative effect is limited to centrist and conservative citizens. However, we find no evidence that international pressure has the power to promote people’s support for the treaty.